Evaluation and relationship analysis of pea protein on structure and heat‐induced gel performance of myofibrillar protein. (27th January 2023) - Chen, Huimin; Wu, Jiulin; Chen, Meizhen; Cai, Xixi; Chen, Xu; Wang, Shaoyun
Abstract: Background: Surimi products occupy a large market in the food industry, and the gel performance is an important index to evaluate them. Thus, it is of great significance and practical value to find better food ingredients to regulate the structure and gel performance of surimi products. In this study, we used pea protein (PP) to restructure fish myofibrillar proteins (MPs) to achieve regulation of protein gel performance. Results: PP could enhance MP gel performance in terms of compressive strength, water‐holding capacity, and some texture parameters. This may be the result of an increasing β ‐sheet content and a decreasing trend in the α ‐helix content, along with enhancements in hydrophobic interactions, nonspecific associations, and ionic bonds in a mixed PP–MP gel. The compressive strength, texture, and water‐holding capacity of MP gel were positively correlated with surface hydrophobicity, active sulfhydryl, turbidity, and β ‐sheet of the mixed PP–MP system. Conclusion: The findings suggest that PP can regulate the gel performance by remodeling the structure of MP. The regulation and correlation analysis between gel performance, structure, and physicochemical properties were explored and established to provide a theoretical basis for improving the quality of surimi products. This study will broaden the application of PP in the field of food processing and provide theoretical guidance for the manufacture of new surimi products. © 2023 Society of Chemical Industry.